1975
DOI: 10.1080/03637757509375884
|View full text |Cite
|
Sign up to set email alerts
|

Stylistic variables as related to source credibility: A content analysis approach

Abstract: R HETORICAL theorists past and present have generally agreed that a lack of stylistic clarity "lowers the speaker in the esteem of his listeners." 1 Unfortunately this well-known principle has not been examined empirically even though research in source credibility abounds in speech and communication journals. A few scholars have measured the effects of intense language, 2 metaphor, 3 simile, 4 or analogy 5 and source credibility concluding that impressions of the source seem less sensitive to stylistic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Imperatives are relationship-dependent and effective to the degree that the respondent deems the speaker trustworthy or credible (Bénabou et al, 2018). An imperative is taken seriously if it originates from a credible source and one way to assess credibility through language is to evaluate personal pronouns (Carbone, 1975). In academic papers, for example, first-person pronouns aid in amplifying an author’s credibility.…”
Section: The Psychology Of Language: Content and Stylementioning
confidence: 99%
“…Imperatives are relationship-dependent and effective to the degree that the respondent deems the speaker trustworthy or credible (Bénabou et al, 2018). An imperative is taken seriously if it originates from a credible source and one way to assess credibility through language is to evaluate personal pronouns (Carbone, 1975). In academic papers, for example, first-person pronouns aid in amplifying an author’s credibility.…”
Section: The Psychology Of Language: Content and Stylementioning
confidence: 99%
“…The management forecast literature finds the market responds favorably to good news forecasts when such forecasts are accompanied by verifiable forward-looking statements, suggesting market participants view such statements as credible (Hirst et al, 2003;Hutton et al, 2003;Lundholm, 1999;Petroni et al, 2000;Ryan, 1997). In the speech literature, Rosenthal (1971) and Carbone (1975) argue that people will accept an empirical statement more readily when it contains verifiable and/or more unambiguous language. The advertising literature also provides evidence that verifiability affects credibility by investigating the difference between verifiable and nonverifiable product qualities (Nelson, 1970(Nelson, , 1974.…”
Section: Perceptions Of Disclosure Credibilitymentioning
confidence: 99%
“…Source and context-oriented analysis examines the characteristics of the communicator, message, medium, context, and recipient (Eisend, 2003;Nawratil, 2013). Regarding the independent variables of the eWoM communication process, results have shown that for the communicator, it is mainly the properties of competence, trustworthiness, similari-ty, and physical attractiveness; for the message style, the language, contents, and structure of the message; and, for the medium, the type of medium, the accuracy with which the information is communicated, and the visual presentation that have an impact on perceived credibility (Bentele & Seidenglanz, 2015;Carbone, 1975;Eisend, 2003;Ohanian, 1990;Robinson & Kohut, 1988).…”
Section: Credibilitymentioning
confidence: 99%